Choose the correct answer

If tan^{–1} (cot θ) = 2 θ, then θ =

We are given that,

tan^{-1} (cot θ) = 2θ

We need to find the value of θ.

We have,

tan^{-1} (cot θ) = 2θ

Taking tangent on both sides,

⇒ tan [tan^{-1} (cot θ)] = tan 2θ

Using property of inverse trigonometry,

tan(tan^{-1} A) = A

⇒ cot θ = tan 2θ

Or,

⇒ tan 2θ = cot θ

Using the trigonometric identity,

Using the trigonometric identity,

By cross-multiplying,

⇒ tan θ × 2 tan θ = 1 – tan^{2} θ

⇒ 2 tan^{2} θ = 1 – tan^{2} θ

⇒ 2 tan^{2} θ + tan^{2} θ = 1

⇒ 3 tan^{2} θ = 1

And .

Thus,

1